African Swine Fever Continues to Be a Problem in Romania and Timiș County - Daniela Moţ; Emil Tîrziu (Scientific Papers Animal Science and Biotechnologies, 2023)
African swine fever continues to evolve in Europe and in our country, even in the last two years of the pandemic, and is currently the main threat to the global swine industry. It affects more than 50 countries on 5 continents, with several epidemiological scenarios. Even this year, Romania was not bypassed by this serious disease, which causes many economic damages: in the case of domestic pigs, in the EU Member States were registered, between 01.01-16.01.2022, 24 outbreaks, of which 22 in Romania. In the same period, 565 outbreaks of PPA were reported in wild boars. Most evolve in Poland (177), Bulgaria (120), Germany (78) and Romania (59). Europe is waiting for an effective vaccine against African swine fever (PPA) by 2024, the main risk to pig health worldwide, being the only way to eradicate the disease. Veterinary services continue their efforts to prevent the spread of the African swine fever virus (PPA), those for the management of disease outbreaks, with the aim of reducing outbreaks and spreading this disease, which already has a history in our country, evolving since 2017 almost constantly.